Association between ratio of fibroblast growth factor 23 (FGF-23) to klotho and phosphate level in chronic kidney disease patient - Khairi, Irham; Kasim, Hasyim; Bakri, Syakib; Parewangi, A.M Luthfi; Umar, Husaini; Seweng, Arifin (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Chronic Kidney Disease (CKD) is a condition in which there is structural and functional damage to the kidneys that lasts more than 3 months, and when there is a decrease in glomerular filtration rate (GFR), phosphate homeostasis is disrupted. FGF-23 acts as a phosphaturic hormone that increases phosphate excretion when there is an increase in serum phosphate levels. The physiological effects of FGF-23 can occur when it binds to Klotho as a co-receptor, where Klotho is mainly produced in the kidneys. Decreased kidney function triggers a decrease in kidney mass, so that Klotho production will decrease. This study aimed to determine the association between the ratio of FGF-23 to Klotho and phosphate levels in patients with CKD. Methods: This was an observational study involving 60 patients with stage 3, 4, and 5 non-dialysis CKD. Serum of FGF-23, Klotho, phosphate, and creatinine were measured using the ELISA method. Statistical analysis was performed using Mann-Whitney, Chi-Square, and Spearman Correlation Tests. Results: The median value of FGF23-Klotho ratio was 0.17. A significant correlation was found between the FGF23-Klotho ratio and phosphate levels (P